Estimating the Low-Cycle Fatigue, Damageability and the Residual Life of the Rotor of High Pressure Turbine Т-100/120-130 unit No 1 used by PJSC "Kharkiv CHPP-5 - Chernousenko, Olga Yuriivna; Peshko, Vitaliy Anatoliyovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
The development of centralized heat supply for large cities requires the estimation of the individual life of each cogeneration power unit that reached the economic life. To extend the service life of the cogeneration turbine Т-100/120-130 unit No 1 used by PJSC "Kharkiv CHPP-5" we analyzed the individual service life using the integrated approach. This approach combines the data of destructive and nondestructive metal examination with the strength and longevity verification computations and the detailed studies of each individual history of the unit operation. Based on the 3D spatial analogue of high pressure rotor and numerical experiment data on the estimation of thermal and stress-strain behavior the damageability of basic metal has been calculated. In the course of the estimation of low-cycle fatigue of high pressure rotor the values of the reduced amplitude of the strain intensity for the most loaded rotor sections were established. When determining the permissible number of start cycles in different thermal states the metal safety factors were experimentally calculated. The computations done showed that a degree of the wear of basic metal makes up 69 %. The metal examination data analysis for the high pressure rotor over the entire operation period is indicative of its satisfactory condition and together with the computation data allows for the extension of the service life of high pressure rotor by 50000 hours and a number of the starts should not exceed 558 starts.